Penyuluhan Perilaku Hidup Bersih Dan Sehat (PHBS) Siswa SDN Balaroa 2 Desa Uwemanje Kecamatan Kinovaro - Doddy Alfayet Lambogo; Wahyuni; Sinta; Elfiana; Asriandini; Ananda Shesilia Lambe; Valen Pawakang; Umi Kalsum; I Gusti Agung Giri Utami,; Fitrahaitunnufus; Sri Ainun J; Alfryana Towesu; Citra Wahyuni; Vidya urbaningrum vidya (CV. Multi Kreasi Media, 2022)
Abstract : Clean and Healthy Living Behavior (PHBS) in schools is a set of behaviors practiced by students, teachers and the school community on the basis of awareness, so that they are able to independently prevent disease, improve their health, and play an active role in creating a healthy environment. Some indicators of PHBS in schools include washing hands with running water and using soap, eating healthy snacks, using clean latrines, exercising regularly, eradicating mosquito larvae, not smoking at school, weighing body weight, measuring height, and throwing garbage at school. This activity is carried out using the lecture method using leaflets and posters. Before and after conducting counseling about PHBS, the presenters gave 3 questions orally. In this activity, demonstration activities were also carried out on how to wash hands properly and correctly. After finishing the presentation of the material, the presenters again gave questions orally about PHBS as many as 3 questions this was done to see how the children responded to the material that had been delivered whether they understood it or not, of the 37 students who attended most of them answered correctly and a small part answer incorrectly. The results of this activity concluded that the knowledge of SDN Balaroa 2 students about PHBS before the counseling was carried out was still very lacking. However, after counseling and demonstrations on how to wash hands properly and correctly the students really understood and were able to practice it again. Keywords: PHBS, School, Washing Hands